How the war was won : command and technology in the British Army on the western front, 1917-1918 - Travers, Timothy (Routledge, 1992)
This important and sometimes controversial book explains what part the British Expeditionary Force played in bringing the First World War to an end. Tim Travers shows in detail how an Allied victory was achieved. He focuses on the British Army on the Western Front in relation to the themes of command and technology, drawing on a wide range of sources from archives in three countries. The book provides new arguments about the origins of mechanical warfare, the role of Douglas Haig, and the near-collapse of the German army by July 1918. Tim Travers argues that, despite poor leadership, the British army ultimately wore its opponent down by using increasing amounts of technology. Complex and detailed information is presented in a clear and readable form. An introductory paragraph at the beginning of each chapter, combined with numerous maps and photos, also makes the book particularly useful for students.